Physical activity and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition. - Lahmann, P; Friedenreich, C; Schuit, A; Salvini, S; Allen, N; Key, T; Khaw, K; Bingham, S; Peeters, P; Monninkhof, E; Bueno-de-Mesquita, H; Wirfält, E; et al. (2007)
There is convincing evidence for a decreased risk of breast cancer with increased physical activity. Uncertainties remain, however, about the role of different types of physical activity on breast cancer risk and the potential effect modification for these associations. We used data from 218,169 premenopausal and postmenopausal women from nine European countries, ages 20 to 80 years at study entry into the European Prospective Investigation into Cancer and Nutrition. Hazard ratios (HR) from multivariate Cox regression models were calculated using metabolic equivalent value-based physical activity variables categorized in quartiles, adjusted for age, study center, education, body mass index, smoking, alcohol use, age at menarche, age at first pregnancy, parity, current oral contraceptive use, and hormone replacement therapy use. The physical activity assessment included recreational, household, and occupational activities. A total physical activity index was estimated based on cross-tabulation of these separate types of activity. During 6.4 years of follow-up, 3,423 incident invasive breast cancers were identified. Overall, increasing total physical activity was associated with a reduction in breast cancer risk among postmenopausal women (P(trend) = 0.06). Specifically, household activity was associated with a significantly reduced risk in postmenopausal (HR, 0.81; 95% confidence interval, 0.70-0.93, highest versus the lowest quartile; P(trend) = 0.001) and premenopausal (HR, 0.71; 95% confidence interval, 0.55-0.90, highest versus lowest quartile; P(trend) = 0.003) women. Occupational activity and recreational activity were not significantly related to breast cancer risk in both premenopausal and postmenopausal women. This study provides additional evidence for a protective effect of physical activity on breast cancer risk.